Flavonoids and other phenolics from Camellia nitidissima chi flowers. Issue 2 (17th January 2023) - Wang, Zhennan; Sun, Bing; Yang, Rui; Jia, Ai-Qun
Abstract: From Camellia nitidissima Chi flowers four undescribed flavonoids, nitidissimol A, nitidissimol B, sexangularetin 3-O-(6''- trans-p -coumarolyglucopyranoside) and sexangularetin 3-O-(2''- trans-p -coumarolyglucopyranoside) (1–4 ), and two previously unreported phenolics, nitidissimol C, D (9, 10 ), were isolated first time along with ten known compounds, kaempferol 3- O -(6''- O - trans - p -coumaroyl)- β -D- glucopyranoside (5 ), kaempferol-3- O -rhamnoside (6 ), Quercetin-3'- O - β -D-glucoside (7 ), kaempferol-7- O - β -D-glucoside (8 ), erythro-guaiacylglycerol- O -4'-coniferyl ether (11 ), threo-guaiacylglycerol- O -4'-coniferyl ether (12 ), protocatechuic acid (13 ), 1, 2-Diethoxybenzene (14 ), ethyl shikimate (15 ), 2, 4, 6-trihydroxybenzoic acid 4- O -allopyranoside (16 ). The structures of the isolated compounds were elucidated by spectroscopic analysis of 1 D- and 2 D-NMR and MS data. Moreover, all isolated compounds (1-16 ) were tested for the antibacterial activity against Xanthomonas oryzae pv. oryzae and their quorum sensing inhibitory activity in Pseudomonas aeruginosa PAO1. However, no one showed signifcant inhibition of X. oryzae pv. oryzae (MIC90 > 0.1 mg/mL), nor did they significantly inhibit the pyocyanin synthesis, which is controlled by quorum sensing in PAO1. Graphical Abstract: UF0001